Analysis Of The Influence Of Nurse Competence, Teamwork, And Supervision Techniques In Patient-Centered Care Implementation At RSUD Dradjat Prawiranegara - Aulia Rahman Hakim, Ari; Rita Wahidi, Kemala; Silviana Mustikawati, Intan (Jurnal Health Sains, 2025)
Patient-focused care is a comprehensive, responsive, and integrated health service approach, with the aim of meeting the diverse needs of patients and their families. This approach emphasizes the importance of the role of health workers, especially nurses, in providing services that are not only oriented towards medical actions, but also towards patient preferences, values, and expectations. Purpose: This study aims to analyze the influence of nurse competence and teamwork on patient-focused care, with supervision techniques as a mediating variable, at Dr. Dradjat Prawiranegara Regional General Hospital, Serang Regency, Banten. Method: The type of research used is quantitative with a descriptive analytical design. Data collection was carried out through questionnaires. Data analysis includes descriptive analysis using the three box method approach, as well as inferential analysis using Structural Equation Modeling–Partial Least Square (SEM-PLS). Population and Sample: The study population was all nurses working in the inpatient ward of Dr. Dradjat Prawiranegara Regional General Hospital, Serang, with a sample size of 250 nurses. Results: The study shows that nurse competence and teamwork have a significant effect on supervision techniques. Furthermore, nurse competence, teamwork, and supervision techniques had both partial and simultaneous effects on the implementation of patient-centered care. The R-square test results also confirmed that these three independent variables simultaneously made a strong contribution to achieving patient-centered care in hospitals.